PENGARUH PERSEPSI PELAJAR SMA X DI JAKARTA TENTANG PENDIDIKAN PARIWISATA TERHADAP MINAT UNTUK MELANJUTKAN PENDIDIKAN DI PERGURUAN TINGGI - Tri Djoko Sulistiyo; Ilham Baharuddin (LPPM and Travel Operation Department Universitas Asa Indonesia, 2019)
The purpose of this study was to know the perceptions about education X senior high school students’ tourism, to find out of interest to continue their studies in college tourism, and find out how much influence the perceptions of high school students in Jakarta about tourism education on the interest to continue education in tourism colleges. Data is collected by spreading questionnaires at random of 87 respondents. The results obtained by the linear regression simply stated that some influence between the perception of interest. Variable Perception has Mean 2,82 and categorized as High. Variable Interest has Mean 2,3 categorized as Low. This evidenced by the determination to 0,241 or 24,1% and perception X senior high school students in Jakarta tourism influence of education interest for continuing their studies of tourism 24,1%, and the remaining 75,9% is influenced by other factors not examined in this study. It can be concluded that the variable perception of Senior High School Students from SMA X about education in tourism low affected to interest continue education in tourism college because perception is only limited to an interpretation of a thing, will better to do research on other variables that can affect the student’s interest.